Psychological issues in cleft lip and cleft palate - Sousa Avinash; Devare Shibani; Ghanshani Jyoti (Wolters Kluwer Medknow Publications, 2009)
Vocational and social issues affect rehabilitation and development of patients with cleft lip and cleft palate. However, psychological problems like lowered self esteem and difficulties in social interaction have also been noted in them. Not many pediatric reconstructive surgery teams have a psychiatrist on their panel. It is likely that psychological problems are higher in incidence than literature actually suggests. Hence it is very essential that such cases are identified by the surgical team to maximize positive outcome of surgery and rehabilitation. This study discusses psychological issues revolving around cleft lip and cleft palate along with lacunae in many psychological research studies.